2014
DOI: 10.4314/njt.v33i3.6
|View full text |Cite
|
Sign up to set email alerts
|

Neural Network Based Model of an Industrial Oil-Fired Boiler System

Abstract: ABSTRACT ABSTRACTIn this study, an oil In this study, an oil In this study, an oil In this study, an oil----fired boiler system is modeled as a multivariable plant with fired boiler system is modeled as a multivariable plant with fired boiler system is modeled as a multivariable plant with fired boiler system is modeled as a multivariable plant with fired flow rate) and two outputs (steam temperature and pressure). The plant parameters are mod fired flow rate) and two outputs (steam temperature and pressure). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Artificial neural network (ANN) has been widely applied in modeling of many nonlinear hydrologic processes such as numerical weather and global climate model [4], rainfall-runoff model [5] and [6], stream flow model [7], [8] and [9], precipitation prediction [10] and [11], rainfall modeling [12], [13] and [14] and simulation of daily temperature [15]. ANN have been trained to perform complex functions in various fields, including pattern recognition, identification, traffic prediction, classification, speech, vision and control systems [16]. According to Khaing andThinn among forty eight (48) studies conducted using ANN between 1988 and 1994, it was found that neural network models produced superior predictions [11].…”
Section: The Upward the Upwardmentioning
confidence: 99%
“…Artificial neural network (ANN) has been widely applied in modeling of many nonlinear hydrologic processes such as numerical weather and global climate model [4], rainfall-runoff model [5] and [6], stream flow model [7], [8] and [9], precipitation prediction [10] and [11], rainfall modeling [12], [13] and [14] and simulation of daily temperature [15]. ANN have been trained to perform complex functions in various fields, including pattern recognition, identification, traffic prediction, classification, speech, vision and control systems [16]. According to Khaing andThinn among forty eight (48) studies conducted using ANN between 1988 and 1994, it was found that neural network models produced superior predictions [11].…”
Section: The Upward the Upwardmentioning
confidence: 99%
“…Te failure rate in the power equipment prediction for a number of input variables afects its performance [36]. Another application of the ANNs is found in the modelling of an industrial oil-fred boiler plant with reliable results [37].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The performance of steam boilers could be assessed based on operational and output parameters which are of primary interest to a researcher or other stakeholders. In a study of an oilfired boiler system, Orosun and Adamu [16] modelled steam boiler as a multivariable plant with two inputs, namely, feed water rate and oil-fired flow rate; and two outputs, which were steam temperature and pressure. The authors modelled the plant parameters using artificial neural network.…”
mentioning
confidence: 99%